Manajemen Kelas Khusus Olahraga di SMA Dalam Mewujudkan Mutu Pendidikan - Amilia Dyah Kumalasari (Media Manajemen Pendidikan, 2019)
The purpose of this study is to: 1) find out the management of the Special Sports Class (KKO) in realizing the quality of education; 2) knowing the carrying capacity and obstacles in carrying out the management of the Special Sports Classes (KKO); 3) determine the effectiveness of the management of the Special Sports Class (KKO) in realizing the quality of education. This research is descriptive qualitative research. This research was conducted at the Playen Gunungkidul 2 Public High School. Data collection methods include interviews, documentation, and observation. Research informants were the principal, teachers, students, committees and supervisors. Data analysis techniques in this study used descriptive qualitative analysis including reduction, data presentation, and conclusion drawing. Based on the results of this study indicate that 1). KKO management in the form of planning, organizing, implementing and evaluating has been carried out well. 2). Carrying capacity in carrying out KKO management is the number of students who receive it. Obstacles in carrying out KKO management are the lack of experts to train students and the lack of sports infrastructure 3). KKO is effective in realizing the quality of education.